2013
DOI: 10.1097/mib.0b013e3182813242
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adalimumab Concentration and Clinical Remission in Patients with Crohnʼs Disease

Abstract: A positive association between serum adalimumab concentration and remission was identified at several time points. A threshold concentration reliably associated with remission was not identified. Further prospective evaluations are needed before recommendations for adalimumab concentration monitoring can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 28 publications
2
79
0
1
Order By: Relevance
“…It has been demonstrated that co-administration of azathioprine with adalimumab had little to no impact on adalimumab clearance. 32,33 In contrast to this the SONIC trial demonstrated that the combination of azathioprine and infliximab increased infliximab trough concentrations by more than 2-fold as compared to infliximab alone. 14 In the rheumatoid arthritis literature concomitant use of IM clearly influences ADA levels, trough levels and clinical response to both infliximab and adalimumab.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that co-administration of azathioprine with adalimumab had little to no impact on adalimumab clearance. 32,33 In contrast to this the SONIC trial demonstrated that the combination of azathioprine and infliximab increased infliximab trough concentrations by more than 2-fold as compared to infliximab alone. 14 In the rheumatoid arthritis literature concomitant use of IM clearly influences ADA levels, trough levels and clinical response to both infliximab and adalimumab.…”
Section: Discussionmentioning
confidence: 95%
“…For this description, we first used CRP as a biomarker. Indeed, CRP has been shown repeatedly to correlate well with sustained clinical response [8,17,18,20], and the relationship between infliximab concentration and CRP was previously investigated in RA [32,33]. Being an anti-TNF-α monoclonal antibody, adalimumab acts as a noncompetitive antagonist of TNF-α and does not act directly on CRP.…”
Section: Figurementioning
confidence: 99%
“…Given that normalization of CRP is associated with sustained clinical response, CRP may be considered as a clinically relevant biomarker [13,[17][18][19][20]. In addition, CRP is increased by TNF-α [21].…”
Section: Structural Modelsmentioning
confidence: 99%
“…Consensus is increasing that trough levels of both anti-TNFa and ADA should be monitored in patients who have undergone anti-TNFa therapy. A few clinical investigators have studied the relationship between anti-TNFa and ADA values in clinical response, disease activity, prognosis, and treatment strategy management [40][41][42][43][44].…”
Section: Biomarkers Predicting Therapeutic Efficacymentioning
confidence: 99%